Inequivalent routes across the mott transition in V 2O 3 explored by X-ray absorption - Rodolakis, Fanny; Haverkort, Maurits W. (Physical review letters, 2010)
The changes in the electronic structure of V2O3 across the metal-insulator transition induced by temperature, doping, and pressure are identified using high resolution x-ray absorption spectroscopy at the V pre-K edge. Contrary to what has been taken for granted so far, the metallic phase reached under pressure is shown to differ from the one obtained by changing doping or temperature. Using a novel computational scheme, we relate this effect to the role and occupancy of the a1g orbitals. This finding unveils the inequivalence of different routes across the Mott transition in V2O3.